The Effect of Music on Moroccan Students’ Acceptance of Kahoot Gamified Quizzing in the EFL Classroom - Mimouni, Abderrahim; Tamer, Youssef (International Journal of Language and Literary Studies, 2020)
Several studies have investigated students’ perceptions toward technologies that add game elements to gamify learning content in English as a Foreign Language (EFL) classroom. Yet, identifying what specific game elements in these technologies have a significant impact on students’ perceptions has not received much attention. This quasi-experimental study aimed at exploring the effect of Kahoot music on Moroccan students’ acceptance of Kahoot gamified quizzing in the EFL classroom. Two intact groups of secondary school students were recruited for this study. One group played Kahoot Gamified Quizzes without music, while the other group played the same quizzes with music. The results of the independent samples t-test showed that the students in both groups perceived Kahoot gamified quizzing positively and that music had no significant effect on their perceptions.